COMMUNICATIVE EXERCISES IN TEACHING GRAMMAR CHARACTERISTICS OF ENGLISH VERBS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In this article, the principles of designing communicative-integrative exercises on teaching English verb and its grammatical features are explored at the level of higher education system students with English language specialty. The research was held by the author by making contrastive analysis of English and Uzbek Verb systems and finding out the field of interferences. While designing the system of exercises, a special attention was paid at the interference cases, the principles of systematic and communicative approach to the creation of exercises.